Ukrainian in Russian Context: Pattern, Folklore and Ethnic Symbols (on the Exsples of Epigraphes in "The Fair at Sorochyntsi" of N.V. Gogol) - Aleksandr V. Savchenko; Anna G. Bodrova (Publishing house "Sreda", 2019)
In this article, from the linguistic and ethnoculturological points of view are analyzed Ukrainian texts of epigraphs in «The Fair at Sorochyntsi» by N.V. Gogol, included in the Russian-language prose, which is an integral part of Russian literature, culture and history. Purpose of the article: This work is an attempt to interpret Ukrainian conceptual symbols, images and metaphors used by the author to create a special atmosphere of Ukrainian identity. Methods: In the study the methods of contextual-pragmatic and lexical analysis are used. In particular, the subject of our study is the Ukrainian texts of the epigraphs to each of the chapters of the above-mentioned literary work, which, due to insufficient knowledge of the Ukrainian cultural context, are far from always deeply understood by the Russian reader and do not always evoke the same associative series as the bearer of the Ukrainian worldview, although close to the Russian one, but still significantly different from it. Results: As a result of the study it is possible to state, that here we deal with the problem of the difference in the cultural perception and understanding the original significance, laid down by N. Gogol in the text and the meaning of his work. It is concluded that the analyzed text of Gogol demonstrates not only the cultural similarity of the two peoples, but, which seems to be more important, the differences in the worldview and way of life of Ukrainians and Russians. The epigraphs in Ukrainian cited by the writer at the beginning of the each chapter serve as a kind of «textual marker», which helps the reader to delve deeper into the content of the text and try to understand not only explicit meaning but also implicit senses implied by the author in its structure.